2010
DOI: 10.1080/08927014.2010.531389
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific detection and quantification of common barnacle larvae from the Japanese coast using quantitative real-time PCR

Abstract: Species-specific detection and quantification methods for barnacle larvae using quantitative real-time polymerase chain reaction (qPCR) were developed. Species-specific primers for qPCR were designed for 13 barnacle species in the mitochondrial 12S ribosomal RNA gene region. Primer specificity was examined by PCR using template DNA extracted from each of the 13 barnacle species, other unidentified barnacle species, and field collected zooplankton samples. The resulting PCR products comprised single bands follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The use of quantitative polymerase chain reaction (qPCR) has proven to be useful for detection of low abundance and cryptic species in aquatic environments (Ficetola et al, 2008), or where morphological characteristics cannot be used for species discrimination (Andree et al, 2011). More recently, qPCR has been shown to be an effective and sensitive tool for the detection and quantification of planktonic organisms (e.g., Vadopalas et al, 2006;Endo et al, 2010), whose identification through classical observational methods is extensive and arduous. More relevantly, qPCR has been used for the detection and quantification of larvae in other species of commercially important mollusks such as abalone (Vadopalas et al, 2006) and invasive alien species such as zebra and golden mussels (Frischer et al, 2002;Endo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of quantitative polymerase chain reaction (qPCR) has proven to be useful for detection of low abundance and cryptic species in aquatic environments (Ficetola et al, 2008), or where morphological characteristics cannot be used for species discrimination (Andree et al, 2011). More recently, qPCR has been shown to be an effective and sensitive tool for the detection and quantification of planktonic organisms (e.g., Vadopalas et al, 2006;Endo et al, 2010), whose identification through classical observational methods is extensive and arduous. More relevantly, qPCR has been used for the detection and quantification of larvae in other species of commercially important mollusks such as abalone (Vadopalas et al, 2006) and invasive alien species such as zebra and golden mussels (Frischer et al, 2002;Endo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More relevantly, qPCR has been used for the detection and quantification of larvae in other species of commercially important mollusks such as abalone (Vadopalas et al, 2006) and invasive alien species such as zebra and golden mussels (Frischer et al, 2002;Endo et al, 2009). For these purposes planktonic abundances were estimated by plotting threshold cycle (C t ) values on the standard curve obtained from template DNA extracted from serial dilution of eggs/larvae (see for instance, Endo et al, 2010). Therefore, one limitation to the devel-opment of such methods relies on the availability of planktonic material of the target species for construction of a proper calibration curve.…”
Section: Introductionmentioning
confidence: 99%
“…qPCR amplification of barcoding genes is recognized as an effective tool for identifying, detecting and quantifying various planktonic organisms in marine environments: sea lice ( coI DNA; McBeath et al , ), crabs ( coI DNA; Pan et al , ), barnacles ( 12s rRNA‐DNA; Endo et al , ) and clams ( 16s rRNA‐DNA; Quinteiro et al , ). The advantages of this molecular technique for studying planktonic communities over other fingerprinting DNA methods such as oligonucleotide hybridization, restriction fragment length polymorphism, random amplified polymorphic DNA, single‐strand conformation polymorphism, denaturing gradient gel electrophoresis and sequencing are several‐fold: pin‐point identification accuracy, sensitivity, rapidity of processing ( c .…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach requires the design of species-specific primers for identification and quantification, thus impeding or preventing the detection of nonnative or invasive species that would not match these primers. Moreover, a general use of 12S sequences as in Endo et al (2010) is also impeded by the insufficient molecular database for this gene in barnacles. Yorisue et al (2012) revealed the settlement-inducing protein complex (SIPC) is species specific and can be potentially used for species identification based on the three barnacle species examined.…”
Section: Introductionmentioning
confidence: 98%
“…Power et al (1999) used mtDNA RFLP to distinguish Chthamalus montagui and C. stellatus larvae in European waters and suggested that the length of the cypris carapace can be a diagnostic parameter for distinguishing these two chthamalid barnacles (O'Riordan et al 2001). Endo et al (2010) used a real-time PCR technique to identify and quantify 13 species of barnacle larvae in Japanese waters and proved the reliability of the method. However, this approach requires the design of species-specific primers for identification and quantification, thus impeding or preventing the detection of nonnative or invasive species that would not match these primers.…”
Section: Introductionmentioning
confidence: 98%